A comparison of food safety programs using the Customizable Tool for Online Training Evaluation. (January 2016) - Howton, Jessica; Keifer, Elizabeth; Murphy, Cheryl A.; Sirsat, Sujata A.; O'Bryan, Corliss A.; Ricke, Steven C.; Crandall, Philip G.; Neal, Jack A.
Abstract: Food safety training for restaurant and food service employees is essential to reduce the risk of foodborne illness. With the large variety of food safety training programs available, it is critical to have an objective evaluation tool, which will allow managers, supervisors or purchasing agents to assessment strengths and weakness among multiple programs. The objective of this study was to use a newly created evaluation tool, the Customizable Tool for Online Training Evaluation (CTOTE) to assess and compare four online food safety training programs currently available to the food service industry. Through a comparison of the objectives of each training programs, a delivery method for training to front-line employees was identified. The preferred training approach was a blended method, which uses multiple delivery methods in a single training module to reinforce of the material being taught. The food safety training program containing the highest overall rating among respondents uses this blended delivery method and was taught at a middle school reading level. Results from this study show supervisors that front-line employees want clear, easy-to-follow instructions, the ability to check their progress, save their work and continue at a later time and include relevant examples and scenarios. Additionally, based on these results, retail employers and food processors can employ the most preferred food safety training methods for their employees. Highlights: Highest rating uses blended delivery method taught at middle school reading level. Employees want clear, easy-to-follow instructions, ability to check progress. Employers should use most preferred food safety training methods.